A RAY OF HOPE THROUGH AYURVEDIC MANAGEMENT IN OSTEOARTHRITIS: A CASE STUDY - Chauhan, *Anshul; Srivastava, Alok; Kutiyal, Priya; Viswas, Sapna Kumari; chauhan, Vandana (International Journal of Ayurveda and Pharma Research, 2018)
Osteoarthritis (OA) is degenerative condition, increasing due to today’s life style and age related changes. It mostly affects woman. A 70 years female patient, housewife by occupation, known case of osteoarthritis since 30 years was admitted in IPD of Panchkarma department with following presenting complaints: continuous pain in both knee joints and pain in lower back and hands. On the basis of strong similarity between etiological factor, symptoms, and Doshika involvement in the etiopathology and complication, OA can be correlated with Sandhigata Vata. There is need to search a safe, effective and less-expensive treatment that can alter the course of the disease. In this condition, Ayurveda is a ray of hope to stop disease progression. Considering these points in mind, Sarvang Abhyang with Narayan Tail, Swedana, Matra vasti with Panchguna Tail was administered in patient for 10 days. After this, Sarvang Patra Pottali Swedana was given for 7 days along with oral medication like Tryodashang Gugglu 2 tablets thrice a day, Tablet Neo 2 tablets twice in day after meal. Activities which were hampered due to symptoms and after 45 days of treatment, patient can perform daily tasks easily with mild pain in some joints and complete relief in others. Ayurvedic management provides better result within limited time periods with least oral medications.